Bibliometric Analysis: Contructivism Approach in Junior High School Geometry Learning in Indonesia (2017-2023) - Ningrum, Sri Adiningsih Utami; Fitriana, Laila (Universitas Ma'arif Lampung, 2024)
Constructivism is a learning theory perspective that strongly influences how mathematics is learned. Since secondary school students are just beginning to recognize and understand abstract thought processes, it is not appropriate to educate them through meaningless memorization, especially in mathematics which is full of abstract symbols. The writing of this article aims to find out the research trends regarding the constructivism approach and to find out the research themes that have the opportunity to be used as research in the future. The method in this research is using bibliometric analysis. Research data obtained through Harzing's Publish or Perish software with Google scholar database, keywords constructivism and junior high school geometry and the result of the maximum number